THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, SELF-EFFICACY, AND DIGITAL LITERACY ON THE COMPETITIVENESS OF BAJAWA COFFEE SECTOR MSMES IN THE INTERNATIONAL MARKET - Kamuri, Klaasvakumok Jehezkielomi; Anabuni, Andrias Umbu Tuku (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The competitiveness of MSMEs is crucial for economic growth and success in international business competition, so this research aims to analyze the influence of entrepreneurship education, self-efficacy, and digital literacy on the competitiveness of micro, small, and medium enterprises (MSMEs) in the Bajawa coffee sector in the global market. This research uses a quantitative approach with an associative type. Data were analyzed using Smart Partial Least Squares (Smart PLS). The research results show that entrepreneurship education does not have a significant impact on competitiveness, while self-efficacy and digital literacy have a significant impact on the competitiveness of Bajawa coffee sector SMEs. With an R-Square value of 75.3%, this study indicates that the combination of self-efficacy and digital literacy greatly contributes to the ability of Bajawa coffee sector SMEs to face global competition. These findings emphasize the importance of developing self-efficacy and digital literacy for Bajawa coffee SMEs to enhance their competitiveness in the international market. Keywords: Entrepreneurship; Self-Efficacy; Digital Literacy; Competitivenes; MSME’s